2021
DOI: 10.3390/ijerph181910503
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Experience of Transcultural Care of Stakeholders and Health Service Users with a Migrant Background: A Qualitative Study

Abstract: Introduction: While European health policies do frequently take into consideration the ideas and experiences of their users, the voices of minority and marginalized communities are not often heard. European healthcare services must address this issue as the number of healthcare users with an MM background increases. Aim: To explore the perspectives of key stakeholders and healthcare users with an MM background on transcultural care in four European countries. Design: Qualitative phenomenological study. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…Poor language competence and communication barriers also impede effective communication, which is very important to the health outcome and thus affects their HSU. Cultural differences would also affect communication (141).…”
Section: Immigrant-specific Factorsmentioning
confidence: 99%
“…Poor language competence and communication barriers also impede effective communication, which is very important to the health outcome and thus affects their HSU. Cultural differences would also affect communication (141).…”
Section: Immigrant-specific Factorsmentioning
confidence: 99%
“…El problema más destacado entre los pacientes y los profesionales enfermeros es la comunicación, no solo por la diferencia de idioma, sino también por la forma en que la cultura puede afectar a la hora de expresarse y la comprensión o significado que se da (23)(24)(25). La comunicación es un elemento terapéutico imprescindible en el cuidado enfermero, la clave para la autonomía, el consentimiento informado y la seguridad y satisfacción en los cuidados recibidos (19).…”
Section: Comunicaciónunclassified
“…Migrant populations experience discrimination more frequently, which constitutes an additional mental health risk factor (Levecque et al, 2009 ; Missinne & Bracke, 2012 ). Although mental health problems are often identified by primary healthcare services, some studies, however, have shown that general practitioners’ (GPs’) therapeutic decisions regarding patients with a migration background are suboptimal: breakdowns in communication and in the relationship between a migrant patient and a GP can be a frequent source of misunderstanding, the time devoted to a consultation is often shorter for migrants, and GPs’ diagnostic, treatment and referral decisions are sometimes biased by their behaviours and beliefs of migrant patients (Gaya-Sancho et al, 2021 ; Lepièce et al, 2014 ; Shannon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%